The Impact of the Pandemic Caused by the SARS-COV-2 Virus on the Functional Fitness of Young Football Players Training from 2017 to 2022 - Szubert, Jędrzej; Kempińska-Podhorodecka, Agnieszka (Journal of Education, Health and Sport, 2025)
Introduction. Functional fitness, which is essential in football, necessitates consistent training, the absence of which may lead to a decline in physical performance and motor coordination. The COVID-19 pandemic significantly restricted social and athletic activities in Poland during the years 2020–2022. The imposed public health measures—such as the closure of sports facilities and the limitation of training to individual formats—adversely affected the motor development of athletes in football clubs. Purpose. The aim of this study is to evaluate the impact of the COVID-19 pandemic on the physical fitness of youth athletes from the Pogoń Szczecin Football Academy (AP Pogoń Szczecin). Material and methods. The study included 83 male participants aged 14, 77 aged 15, 84 aged 17, and 75 aged 19. Selected fitness assessments—including the Beep Test, 30-meter sprint, and Repeat Sprint Ability (RSA) Test—were used to evaluate the motor abilities (speed and endurance) and recovery capacity of athletes from the Pogoń Szczecin Football Academy (AP) between 2019 and 2022. The tests were conducted under the supervision of trained coaching staff using electronic timing gates.Results. In contrast to the 17- and 19-year-old football players, the COVID-19 pandemic led to a decline in sprint performance and Beep Test results among the 14- and 15-year-old athletes. In the younger age groups, performance began to improve following the resumption of regular training; however, within a two-year period, it did not fully return to pre-pandemic levels.Conclusion. The COVID-19 pandemic, restrictions on access to sports infrastructure, and the shift to individually conducted training sessions with limited coach supervision had a negative impact on the functional capacity of youth football players.